2022
DOI: 10.1186/s12957-022-02535-z
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of ceRNA network reveals potential prognostic Hint1-related lncRNAs involved in hepatocellular carcinoma progression

Abstract: Background Hint1 is a novel tumor suppressor gene, and inactivation of its expression is closely associated with the carcinogenesis of a variety of malignancies. The effects of Hint1 deficiency on the competing endogenous RNA (ceRNA) regulatory network in the context of HCC remains to be fully characterized. This study aims to explore Hint1-related hub lncRNAs in HCC and to establish a reliable prognostic model for HCC patients based on these hub lncRNAs. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…For example, Xue et al reported that lncRNA ZEB1-AS1 inhibited HCC progression through miR-23c [ 69 ]. In another study, a prognostic signature and a nomogram integrating three lncRNAs were constructed for HCC patients [ 70 ]. Further studies that integrated multicenter datasets and different types of RNA genes are needed to test the results.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Xue et al reported that lncRNA ZEB1-AS1 inhibited HCC progression through miR-23c [ 69 ]. In another study, a prognostic signature and a nomogram integrating three lncRNAs were constructed for HCC patients [ 70 ]. Further studies that integrated multicenter datasets and different types of RNA genes are needed to test the results.…”
Section: Discussionmentioning
confidence: 99%